The use of fecal microbiota transplantation in the treatment of intestinal diseases - Gabriela Ręka; Emilia Nowak; Dominika Psiuk; Agata Rocka; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Introduction and purpose             Fecal microbiota transplantation (FMT) is a process of transferring gut microflora from a healthy donor to a recipient. It is indicated that the human distal gastrointestinal tract consists of more than 1000 species of bacteria, which have an impact on local and systemic processes related to immunity, nutrition and the gut-brain axis. The growth of new bacterial species, reduction of microbial variety or big changes in the ratio between them can lead to a dysbiosis. The relationship between intestinal microbiota and some systemic diseases is seen. The study aimed to present the state of knowledge on FMT in the treatment of intestinal diseases. Publications from the last 5 years from the Pubmed database were included. A brief description of the state of knowledge Intestinal diseases constitute the main group of indications for FMT. FMT can be delivered via upper or lower gastrointestinal routes. The review presents different studies concerning the usage of FMT. Among them, recurrent Clostridium difficile infection, colitis ulcerosa, Crohn's disease and irritable bowel syndrome are mainly indicated in the literature. FMT might find its application also in a treatment of multidrug-resistant organisms colonization, antibiotic-associated diarrhea, gut acute graft-versus-host disease and radiation enteritis. There is a possibility of the occurrence of adverse events from the digestive tract after FMT. However, the studies evaluate them as mostly mild and transient. In some cases it was necessary to repeat FMT to achieve a satisfactory final result. Conclusions Fecal microbiota transplantation gives hope for a safe and effective method of treatment of certain intestinal diseases. There is a need for conducting further analysis of the method.